2018
DOI: 10.1167/iovs.17-22504
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Audiovisual Integration in the Ventriloquism Effect But Pervasive Deficits in Unisensory Spatial Localization in Amblyopia

Abstract: PURPOSE. Classically understood as a deficit in spatial vision, amblyopia is increasingly recognized to also impair audiovisual multisensory processing. Studies to date, however, have not determined whether the audiovisual abnormalities reflect a failure of multisensory integration, or an optimal strategy in the face of unisensory impairment. We use the ventriloquism effect and the maximum-likelihood estimation (MLE) model of optimal integration to investigate integration of audiovisual spatial information in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…In a study by Rauschecker and Harris (1983), the superior colliculus elicited a more rigorous response in eyelid-sutured than in normal cats. Despite the previous evidence on increased neuronal responses to auditory information after different types of visual sensory deprivation, the causal or Recent studies on auditory localization performance in humans diagnosed with amblyopia argue against compensatory performance in the auditory modality (Richards et al, 2018(Richards et al, , 2019a. These reported reduced auditory localization skills in individuals with amblyopia compared to sighted controls.…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…In a study by Rauschecker and Harris (1983), the superior colliculus elicited a more rigorous response in eyelid-sutured than in normal cats. Despite the previous evidence on increased neuronal responses to auditory information after different types of visual sensory deprivation, the causal or Recent studies on auditory localization performance in humans diagnosed with amblyopia argue against compensatory performance in the auditory modality (Richards et al, 2018(Richards et al, , 2019a. These reported reduced auditory localization skills in individuals with amblyopia compared to sighted controls.…”
Section: Discussionmentioning
confidence: 88%
“…Recent studies on auditory localization performance in humans diagnosed with amblyopia argue against compensatory performance in the auditory modality ( Richards et al., 2018 , 2019a ). These reported reduced auditory localization skills in individuals with amblyopia compared to sighted controls.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[21][22][23][24] Surprisingly, a recent investigation by our laboratory suggested that people with amblyopia may also have greater difficulty localizing sounds, even in complete darkness. 25 As with spatial acuity in the human visual system, spatial acuity in the auditory system follows a developmental trajectory through childhood. Binaural localization is immature at birth, but improves dramatically during the first several years of life.…”
mentioning
confidence: 99%